Overview of foreign exchange department of Jamuna Bank Limited (Mirpur-10) branch - Ridoy, Sazzad Rahman (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.